Reduced healthcare spending can improve patient health. Outcome of a national survey - Benussi, Fulvio Oscar (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
In Italy, nephropathic patients on extracorporeal haemodialysis number around 50,000 and, on the basis of the data we will present in this article, only 3,391 of them perform home dialysis. This figure was obtained from the answers to the questionnaire we sent to local health authorities and hospitals throughout Italy. The results of the survey carried out highlight the urgent need to promote the dissemination of all available methods to enable an increasing number of patients to perform dialysis at home.